Lipidomics Analysis of Outer Membrane Vesicles and Elucidation of the Inositol Phosphoceramide Biosynthetic Pathway in Bacteroides thetaiotaomicron - Mariana G. Sartorio; Ezequiel Valguarnera; Fong-Fu Hsu; Mario F. Feldman (Microbiology Spectrum, 2022)
ABSTRACT Approximately one-third of the human colonic microbiome is formed by bacteria from the genus Bacteroides. These bacteria produce a large amount of uniformly sized outer membrane vesicles (OMVs), which are equipped with hydrolytic enzymes that play a role in the degradation of diet- and host-derived glycans. In this work, we characterize the lipid composition of membranes and OMVs from Bacteroides thetaiotaomicron VPI-5482. Liquid chromatography-mass spectrometry (LC-MS) analysis indicated that OMVs carry sphingolipids, glycerophospholipids, and serine-dipeptide lipids. Sphingolipid species represent more than 50% of the total lipid content of OMVs. The most abundant sphingolipids in OMVs are ethanolamine phosphoceramide (EPC) and inositol phosphoceramide (IPC). Bioinformatics analysis allowed the identification of the BT1522–1526 operon putatively involved in IPC synthesis. Mutagenesis studies revealed that BT1522–1526 is essential for the synthesis of phosphatidylinositol (PI) and IPC, confirming the role of this operon in the biosynthesis of IPC. BT1522–1526 mutant strains lacking IPC produced OMVs that were indistinguishable from the wild-type strain, indicating that IPC sphingolipid species are not involved in OMV biogenesis. Given the known role of sphingolipids in immunomodulation, we suggest that OMVs may act as long-distance vehicles for the delivery of sphingolipids in the human gut. IMPORTANCE Sphingolipids are essential membrane lipid components found in eukaryotes that are also involved in cell signaling processes. Although rare in bacteria, sphingolipids are produced by members of the phylum Bacteroidetes, human gut commensals. Here, we determined that OMVs carry sphingolipids and other lipids of known signaling function. Our results demonstrate that the BT1522–1526 operon is required for IPC biosynthesis in B. thetaiotaomicron.